Capsular Contraction Syndrome. Review. Methods of Prevention and Treatment. Part 2 - D. I. Ivanov; V. N. Nikitin (Oftalʹmologiâ)
The article describes the existing methods of preventing the occurrence and progression of capsule bag fibrosis. The types of used treatment are listed and structured. Key aspects of the principles of surgical treatment are highlighted. They are aimed to eliminate the dislocation of the IOL-fibrous capsular bag complex. Special attention is paid to the methods of suture and sutureless fixation of the IOL to the sclera or iris. The author’s techniques are given. Variants of fixing devices were used. The risks of possible complications were analyzed. Conclusion: capsular syndrome is an actual problem that requires attention and search for optimal treatment methods, depending on comprehensive assessment of the initial condition.